IMPLEMENTASI PENDIDIKAN MULTIKULTURAL DALAM PRAKTIK PENDIDIKAN - Atin Supriatin; Aida Rahmi Nasution (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2017)
Indonesia is a multicultural country consisting of different tribes, languages ​​and religions. This diversity, on one hand, is one of the advantages and wealth of the nation that must be maintained. But on the other hand, this diversity can be a potential conflict in the midst of society. Therefore, the understanding of the motto of "bhineka tunggal ika" should be instilled to the young generation from an early age so that they can play a role in maintaining unity amid the pluralism of the nation. One effort that can be realized in order to respond to this problem is to implement the concept of multicultural education (multicultural education) in education in Indonesia. This article seeks to discuss the concept of multicultural education and its practice in education in Indonesia.